Sensory Evaluation of Gulu Naga Ijo as a Complementary Finger Food Product - Fauziah Putri, Novita; Aji, Arif Sabta; Aprilia, Veriani; Salfarino, Ryan; MZ, Rama Beka Sariy; Triwahyuni, Novi; Triastanti, Resti Kurnia (Indonesian Journal of Human Nutrition, 2023)
The development of four-star complementary foods for breast milk (Makanan Pendamping ASI or MP-ASI) products signifies the inclusion of four nutritional elements, i.e. carbohydrates, animal protein, vegetable protein, and vegetables, needed to support the growth and development of children. This study aimed to determine the sensory evaluation, including taste, texture, aroma, appearance, and color, as well as the acceptability test of finger food products known as “Gulu Naga Ijo” made from a combination of corn, eggs, dragon fruit, and green bean flour. This research was an experimental study with a completely randomized design (CRD) on five treatment variations (P0: 0% composite flour, P1: 25% composite flour, P2: 50% composite flour, P3: 75% composite flour, and P4: 100% composite flour). This study revealed a significant difference in sensory evaluation of products and composite flour substitution (p<0.05). Overall, two samples (P1 and P3) obtained the highest preference from the panelists in the sensory evaluation, prompting for test acceptability score of the products The acceptability test for toddlers resulted in scores of 1.3 for formula P3 and 1.8 for formula P1. The use of composite flour has a significant effect on the sensory evaluation and acceptance of finger food product development.